PENERAPAN METODE TEMPLATE MATCHING DALAM MENGANALISA CACAT PADA KEPING PCB - Mustika Sonsank; Yasdinul Huda; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
Template matching is one of the techniques in digital image processing function to match each part of an image with an image into a template (reference). Template matching method is often used to identify the image of the character of letters, numbers, fingerprints, and other matching applications. In this final project will be made on the damage detection applications PCB track, this is due to PCB circuit paths that are too small and tight, so the detection manually, by using on the human eye will take a long time and a high degree of exhaustion. Making an application is intended to speed up the process detection of damage to the PCB track. The method used in this application is a method of Template Matching with Delphi programming language. Algorithms method Template Matching will classify the object, by comparing the image with a reference PCB with PCB input image. The results of applications  showed that PCB track damage detection method can detect with Template Matching damage on  the PCB track, which is marked by a red rectangular box if there is damage on  the PCB. If there is no damage on the PCB, then a warning box appears informing the PCB in good condition, without any defects. Keywords: PCB, Template Matching Method, Image Processing, Delphi